The clinical value of human leukocyte antigen HLA-DRB1 subtypes associated to Graves' disease in Romanian population. (July 2014) - Martin, Sorina; Dutescu, Monica Irina; Sirbu, Anca; Barbu, Carmen; Albu, Alice; Florea, Suzana; Fica, Simona
<x xml:space="preserve">Abstract</x> The aim of this study was to identify the primary susceptibility HLA-DRB1 alleles associated with GD in Romanian population and to seek whether specific HLA-DRB1 haplotypes are associated with differences in the clinical presentation of GD at diagnosis. Molecular typing of HLA-DRB1 alleles was performed in 77 Romanian Caucasian GD patients and 445 racially matched controls. In GD patients, age, presence of eye disease, goiter grade, autoantibody status and titer, TSH, FT4, FT3, TT3 levels were recorded at diagnosis. The allelic frequencies of HLA-DRB1*03 (41.55% vs. 17.75%, p < 0.0001, χ2 = 20.81) and DRB1*11 (42.85% vs. 30.56%, p = 0.045, χ2= 3.98)were higher, whereas those of HLA-DRB1*01(3.89% vs. 16.40%, p = 0.007, χ2 = 7.281) and DRB1*15 (10.38% vs. 21.34%, p = 0.038, χ2 = 4.309)were lower in GD patients than in controls. FT4/TT3 ratio (p = 0.015) and anti-thyroglobulin antibodies (p = 0.024) were higher in *03/11 patients compared to *X/X, *11/Z, *03/Y patients (where X is any other allele than *03 and *11, Y is any other allele than *11, Z is any other allele than *03). In conclusion, HLA-DRB1*03 and DRB1*11 may be the primary susceptibility HLA-DRB1 alleles associated with GD in Romanian population, whereas HLA-DRB1*01 and DRB1*15 seem to be protective. At diagnosis, HLA-DRB1*03/11 GD patients had higher FT4/TT3 ratio and anti-thyroglobulin antibody levels.